Aflasafe MW02 for Malawi - CGIAR Research Program on Agriculture for Nutrition and Health (2017)
Aflasafe MW02, a biocontrol product developed for use in maize and groundnut in Malawi, has reached the final stage of piloting. A registration dossiers has been submitted to the regulatory authority.